Understanding the rift, the (still) uneasy bedfellows of History and Organization Studies - Greewood, Anna; Bernardi, Andrea (doi: 10.1177/1350508413514286, 2014)
Although the use of History has become increasingly discussed and more widely applied within Organization Studies (OS), its relevance for OS still remains far from centrally accepted. This article historicizes the relationship between Sociology and History as a means of better understanding the tensions, perceived and real, that exist between History and Organization Studies. In particular we analyse three differences of epistemological standpoint (method, objectivity and usefulness) that are commonly seen as the foundation stones to incompatibility. Perhaps surprisingly for an analysis of apparent disciplinary differences, we find that these distinctions in terms of approach, once closely examined, are rarely clear-cut and historians and OS scholars are frequently closer in intention and method than they are distant. However, despite their large intersection of interests, we argue that important distinctions between the two fields should be acknowledged. Our contribution to the debates over the need for more historical approaches within OS therefore centrally rests on abandoning aspirations for fully integrative models of working together, in favour of cooperative modes that concede the fields’ differences. This subtle shift of emphasis will, we believe, greatly benefit OS scholars who hope to include historical perspectives in their work.